2021
DOI: 10.2147/ijgm.s320998
|View full text |Cite
|
Sign up to set email alerts
|

HOTAIR Facilitates Endocrine Resistance in Breast Cancer Through ESR1/miR-130b-3p Axis: Comprehensive Analysis of mRNA-miRNA-lncRNA Network

Abstract: Background To summarize the regulatory role of mRNA-miRNA-lncRNA network associated with endocrine therapy resistance (ETR) in breast cancer. Methods We analyzed the differentially expressed genes (DEGs), differentially expressed lncRNAs (DELs), and differentially expressed miRNAs (DEMs) in long-term estrogen-deprived (LTED) estrogen receptor (ER)-positive breast cancer cells (LTED MCF7) (modeling relapse on endocrine therapy) and MCF7 cells in the presence of estrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Of note, some of these mutant TP53 -upregulated miRNAs have previously been shown to reduce ER expression in breast cancer models such as miR130b and miR301 (Supplementary Fig. 4e ) 55 , 58 , 59 .…”
Section: Resultsmentioning
confidence: 98%
“…Of note, some of these mutant TP53 -upregulated miRNAs have previously been shown to reduce ER expression in breast cancer models such as miR130b and miR301 (Supplementary Fig. 4e ) 55 , 58 , 59 .…”
Section: Resultsmentioning
confidence: 98%
“…Apart from the p21 WAF1 /CIP1 and HOXA5 pathways, the most commonly acknowledged mechanism of HOTAIR is through the axis of microRNA (miR) and downstream signaling molecules. These axes include but are not limited to the following: HOTAIR/miR-222-3p/Cyclin Dependent Kinase 19 axis ( 46 ), HOTAIR/specificity protein 1/miR-199a axis ( 47 ), HOTAIR/miR-29b/phosphate and tension homology deleted on chromosome 10/PI3K axis ( 48 ), HOTAIR/miR-203/zinc finger E-box binding homeobox 1 axis ( 49 ), HOTAIR/estrogen receptor 1/miR-130b-3p axis ( 50 ), HOTAIR/miR-34a/Janus kinase 2/STAT3 axis ( 51 ), HOTAIR/miR-129-5p/ribosomal protein L14 axis ( 52 ), HOTAIR/miR-129-5p/frizzled class receptor 7 axis ( 53 ) and HOTAIR/miR-149-5p/doublecortin-like kinase 1 axis ( 54 ). Furthermore, HOTAIR also interacts with several classic signaling pathways, which are commonly involved in oncogenesis, such as CCL22 signaling ( 55 ), the Wnt/β-catenin signaling pathway ( 56 ), EZH2 and H3K27 methylation signaling ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study on the clinical treatment of BC patients with E2 observed that HOTAIR can mediate endocrine therapy resistance via the hub gene ESR1 by targeting miR-130b-3p in BC patients [ 76 ]. It can also mediate trastuzumab resistance in BC cell lines by upregulating TGF-β, vimentin and Snail expression, downregulating E-cadherin levels, and increasing the methylation of PTEN gene (Fig.…”
Section: Hotair As a Driver Of Breast Cancermentioning
confidence: 99%